Karakteristik Responden Penderita Diabetes Melitus Tipe 2 Dengan Resiko Kaki Diabetik - Kiki Hardiansyah Safitri; Maria Sri Hartati; Alfi Pratama (ITKES Wiyata Husada Samarinda, 2017)
Patients with diabetes mellitus have different characteristics such as age, sex, duration of suffering, work, and education which can affect the risk of diabetic foot so that it can be at 15% risk of having diabetic foot complications during his lifetime and 70% relapse in 5 years. Long-term complications of diabetes mellitus both microvascular and macrovascular can. causing insufficiency of blood flow to the legs, which leads to infection, ulcers and ends in amputation. Aim to find out the relationship between the characteristics of respondents with type 2 diabetes mellitus and the risk of diabetic foot. This type of research uses descriptive analytic with cross sectional design. Conducted from March to April 2018. The sample in this study amounted to 46 respondents who had not yet experienced diabetic foot ulcers, with Consecutive sampling technique. Data were collected by respondent characteristic questionnaires and screening of Inlow's 60 Second Foot Screen Screening Tool. Data analysis using Fisher's Exact Test was obtained by age (p = 0.002; OR = 21.88), gender (p = 0.047; OR = 5.40), duration of suffering (p = 0.042; OR = 6.22) , work (p = 0.00, OR = 11.73) and education (p = 0.025; OR = 6.45) have a significant relationship with the risk of diabetic foot. The results showed that the characteristics of respondents (age, sex, duration of suffering, work and education) had a significant relationship with the risk of diabetic foot. It is expected that community nurses care more about screening diabetics, because the characteristics of sufferers can increase the risk of diabetic foot.